Faktor-Faktor yang Mempengaruhi Harga Saham pada Industri Retail Trade and Whole Sale - Mulia Inda Purwati (JUMANJI (JURNAL MANAJEMEN JAMBI), 2022)
This study is performed to examine the effect of Current Ratio (CR), Debt To Equity Ratio (DER), Total Asset Turnover (TATO), Return On Equity (ROE) and Earning per Share (EPS) toward stock price on Retail trade and whole sale that is listed on the Indonesian Stock Exchange from 2009 to 2012. Sampling technique used here is purposive sampling to obtain samples in accordance with predeterminan criteria. Method of data analysis used is the multiple linear regression analysis, hypothesis test using f-statistic to examine the mean of mutual, t-statistic to examine partial and test the coefficient of determination. Data processing was carried out using SPSS 16.0. In addition, classical assumption is also performed including normality test, multicolinearity test, autocorrelation test and heteroscedasticity test.